Psychosomatics of the impact of dental radiological investigations on the patient - Lucian Josan; Alina Ormenisan; Elina Teodorescu; Laura Stef; Andreea Salcudean; Mariana Pacurar (Amaltea Medical Publishing House, 2023)
Radiological diagnosis in dental medicine is of overwhelming importance, helping the dentist to develop and justify his final diagnosis. They are increasingly common situations where diagnosis can only be determined radiologically. It is the patient's right to be informed about his or her state of health and at the same time we add a doctor's duty. In our material, we tried to highlight the impact on the patient the conducting and communicating the outcome of radiological investigations, to prove that there is fear of irradiation and to understand how the radiological image that demonstrates a poor orodental health entails the need for rehabilitation. This statistical study was performed on a total of 223 subjects (128 female subjects and 95 male subjects). The subjects of the study were asked questionnaires whose questions highlight the confirmation or rejection of the proposed objectives. The results obtained will show to what extent the patients have quantified the requirements of the questionnaires. Obtaining responses with a slightly surprising character certifies the rigor of our research.